Determinant Factors that Influence the Prevalence of Gonorrhea in Female Sex Wokers in Yogyakarta - Lilis Suryani (Formosa Journal of Sustainable Research, 2023)
Gonorrhea is the leading cause of sexually transmitted infections (STIs) caused by Neisseria gonorrhoeae. Commercial sex workers are vulnerable to infection with STIs. The aim was to determine the prevalence of gonorrhea among commercial sex workers in Yogyakarta and the risk factors. The research design is cross-sectional. 43 commercial sex workers in Kota Yogyakarta had their cervical secretions taken for the diagnosis of gonorrhea. Demographic data and subject behavior were obtained through interviews. The results showed that the majority of respondents had a junior high school education, and 25.6% were infected with gonorrhea. The incidence of gonorrhea was not related to the behavior. Age is related to the incidence of gonorrhea. The prevalence of gonorrhea in Kota Yogyakarta is 25.6% and age is a risk factor for gonorrhea